Effect of dietary supplementation with essential oils and a Bacillus probiotic on growth performance, diarrhoea and blood metabolites in weaned pigs - B. F. Tan; T. Lim; W. Boontiam (My University, 2020)
Context Dietary supplementation of essential oils or in combination with a Bacillus probiotic was investigated as an antibiotic growth promoter for weaned pigs. Aims To evaluate the effect of essential oils (i.e. thymol and carvacrol mixture) or in combination with a probiotic strain (i.e. Bacillus subtilis PB6) on the growth performance, diarrhoea incidence, ammonia emission and serological profiles of weaned pigs. Methods A total of 96 crossbred ([Yorkshire × Landrace] × Duroc) weaned pigs were randomly allotted to one of six treatments based on sex and initial bodyweight. Each group was distributed into four replicates with four pigs each according to a randomised complete block design. The treatments were: (i) positive control, basal diet supplemented with colistin 150 g/tonne and amoxicillin 200 g/tonne; (ii) negative control, basal diet without supplementation; (iii) T3, basal diet supplemented with essential oils 300 g/tonne; (iv) T4, basal diet supplemented with essential oils 600 g/tonne; (v) T5, basal diet supplemented with essential oils 1000 g/tonne; and (vi) T6, basal diet supplemented with essential oils 300 g/tonne diet and Bacillus probiotics 1000 g/tonne. Key results The piglets fed with supplements had a significantly higher average daily gain and lower incidence of diarrhoea than the piglets in the negative control (P = 0.001). Feeding the essential oils alone or in combination with probiotics significantly reduced faecal ammonia emission (P = 0.027) and blood urea nitrogen (P = 0.039), while markedly increasing the serum immunoglobulin G concentration of weaned pigs compared with the negative control treatment (P = 0.014). The difference in time of blood collection had significant effects on blood urea nitrogen and immunoglobulins (P = 0.001). However, no significant differences emerged in average daily feed intake, gain: feed ratio, feed efficiency and antibody against swine fever among the treatments. Conclusions Diet supplementation with essential oils or in combination with probiotics improved growth performance and immunity, and lowered ammonia emissions and diarrhoea incidence of weaned pigs. Implications These findings provide a basis for the application of phytogenic compounds and probiotics as antibiotic growth promoter alternatives in post-weaning diets for pigs.
Keywords: Animal Nutrition and Physiology